An econometric study of the impact of GDP on government spending in Syria using the Wagner law test during the period 1985-2021 - زرطيط, بسام; عبد الهادي الرفاعي , (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study aimed to test Wagner's law in Syria, to show the direction of the dialectical relationship between public spending, both its current and investment parts, and the gross domestic product in Syria. This study was conducted based on time series data for the two aforementioned variables published in the statistical compilation issued by the Central Bureau of Statistics during the period. From 1985-2021. In this study, the ARDL methodology was used to test cointegration between variables, and to demonstrate the quality of the relationship between output and spending, in addition to Granger causality to demonstrate the direction of this relationship. The study concluded that the variables of the Syrian economy are not subject to Wagner's Law, and it also showed the weakness of the relationship between these variables and their illogicality in the Syrian case.